The Influence of Human Resource Development, Work Environment and Innovation Culture on the Effectiveness of the State Senior High School Teacher Profession in the Riau Islands Province - Sumarno; Kasful Anwar; M. Syahran Jailani (Cita konsultindo, 2025)
The influence of human resource development, work environment, and innovation culture on the effectiveness of state high school teachers in the Riau Islands. This quantitative study used a survey with a population of all state high school teachers in the Riau Islands. The sample consisted of 30 trial respondents and 149 research respondents, selected using stratified random sampling techniques. The research instrument was a Likert scale questionnaire, and the data were analyzed using path analysis techniques. The results showed that the greatest influence was from human resource development (X1) on the profession effectiveness of teacher (X4), with a path coefficient of 0.811 and a contribution of 65.77%. The lowest influence was from the work environment (X2) on the profession effectiveness of teacher (X4) through a culture of innovation (X3), with a path coefficient of 0.356 and a contribution of 12.67%. In conclusion, there is a positive influence of human resource development, work environment, and innovation culture on teacher effectiveness. The implication is that the better the development of human resources, the work environment, and the more innovative the culture, the higher the teacher's. effectiveness